Effects of pH on the Stability of Monascus purpureus Red Yeast IR-64 Rice (MpRYR) Extract - Shaleha, Resha Resmawati; Yuliana, Anna; amin, Saeful; Sumiwi, Sri Adi; Levita, Jutti (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Monascus purpureus red yeast rice (MpRYR), popularly known as angkak, is a Chinese fermented rice health product. The red pigments and monacolin K contained in MpRYR are sensitive to various factors, including acidity, temperature, oxidation, and light; thus, MpRYR is unstable and susceptible to damage during storage and processing. It was reported that monacolin K in red yeast rice solution was easily degraded under thermal treatment at 85–121°C, and the absorbance of MpRYR extract increased at an alkaline pH. This work aimed to study the effects of pH on the stability of pigment extract MpRYR. MPRYR was purchased from Raja Godhong herbal supplier and extracted with 70% ethanol for 3 × 24 h. The resulting MpRYR extracts were subjected to various pH conditions, and the pH and absorbance were measured, and the degradation rate of MpRYR extracts was calculated. The initial pH of MpRYR extract is 5.75, which increased to 5.97 (+3.82%) at 3 h. The MpRYR extract was more stable in an acidic medium with a degradation rate of 3.80% at 3 h. Research results suggest that acidic conditions are preferable for storing and formulating MpRYR-based products to preserve their functional efficacy.